Analysis of Fiqh Siyasah on The Effectiveness of Driver's License Service Im-plementation In the Jurisdiction of Tapanuli Selatan Police Department, Padang Sidimpuan City - Harahap, Rahma Yani; Marpaung, Zaid Al-Fauza (IHSA Institute, 2025)
A Driver's License (SIM) is an important document that must be possessed by every driver in Indonesia. The existence of a driver's license (SIM) serves as a legal document for the community to be able to drive motor vehicles legally and avoid legal sanctions from the police. Therefore, public services in the issuance of driver's licenses, particularly in the jurisdiction of the South Tapanuli Police (Tapsel), Padang Sidempuan City, must comply with the provisions of Article 21 of Law Number 25 of 2009 concerning Public Services. However, in practice, SIM services in that area are considered not optimal. From the perspective of fiqh siyasah, the SIM service should reflect the principle of public welfare (maslahah ‘ammah) and align with the maq??id syar?‘ah, particularly in the aspect of protecting life (?if? al-nafs). Fiqh siyasah views that public policy, including traffic regulations, should aim to maintain order and the safety of society as a whole. In this context, the suboptimal implementation of SIM services indicates a gap between positive legal policies and the values of justice in Islam. This research uses an empirical legal approach through interviews, field observations, and the distribution of questionnaires. The data collected includes primary data, secondary data, as well as relevant scientific literature sources. The research results show that although there is a strong legal basis, the implementation of SIM services in the jurisdiction of Polres Tapsel has not yet fully met the principles of good public service, both in terms of efficiency, transparency, and accountability. According to the scholars of fiqh siyasah, the service should be carried out fairly, firmly, and consistently for the sake of achieving the welfare of the community. Therefore, there is a need to improve the quality of SIM services by the police so that the public becomes more law-abiding and orderly in traffic